Do soft sediment deformations in the Late Triassic and Early Jurassic of the UK record seismic activity during the break-up of Pangea?. Issue 6 (December 2021) - Laborde-Casadaban, Marine; Homberg, Catherine; Schnyder, Johann; Borderie, Sandra; Raine, Robert
Abstract: The lagoonal and shallow marine sediments of the Penarth Group in the UK span the Triassic–Jurassic boundary. These sediments contain several disturbed levels with soft sediment deformations (SSDs), such as synsedimentary faults, injective domes, recumbent folds and slumps that are recognised in most basins from SW England and South Wales to NW Northern Ireland. Field observations, notably the close link of the SSDs to active faults, attest an earthquake origin of the SSDs. Fluids, faults, overpressure and lithology guided the style of the SSDs and their distribution in the sedimentary sections. Analysis of the directional data relating to SSDs in each disturbed level shows preferred orientations of deformation, which correspond to the local state of stress at the time. We favour a series of earthquakes, rather than a single mega-event as a trigger of the observed features. The active local extensional tectonic context was driven by the opening of the Permo-Triassic basins in Western Europe. The data from the SSDs in the UK suggest the development of a multi-directional, mosaic-style extensional context to occur during this early phase of the break-up of Pangea. Our integrated tectonic/sedimentary study suggests that directional data from faults, injective domes, recumbent folds and slumps preserved in sediments are reliable to reconstruct past seismic activity and basin geodynamics.